Tuning the Supramolecular Structure and Function of Collagen Mimetic Ionic Complementary Peptides via Electrostatic Interactions - Pal, Vijay Kumar (Langmuir : the ACS journal of surfaces and colloids, 2020)
Collagen, the most abundant component of natural ECM, has attracted interest of scientific communities to replicate its multihierarchical self-assembling structure. Recent developments in collagen mimetic peptides were inclined toward the production of self-assembling short peptides capable of mimicking complex higher order structures with tunable mechanical properties. Here, we report for the first time, the crucial molecular design of oppositely charged collagen mimetic shortest bioactive pentapeptide sequences, as a minimalistic building block for development of next-generation biomaterials. Our rational design involves synthesis of two pentapeptides, where the fundamental molecular motif of collagen, that is, Gly-X-Y has been mutated at the central position with positively charged, lysine, and negatively charged, aspartate, residues. Depending on their overall surface charge, these peptides showed high propensity to form self-supporting hydrogel either at acidic or basic pH, which limits their biomedical applications. Interestingly, simple mixing of the two peptides was found to induce the coassembly of these designed peptides, which drives the formation of self-supporting hydrogel at physiological pH and thus enhanced the potential of exploring these peptides for biomedical purposes. This coassembly of ionic peptides was accompanied by the enhancement in the mechanical stiffness of the gels and reduction in overall zeta potential of the combined hydrogel, which provides the evidence for additional electrostatic interactions. Furthermore, the thixotropic nature of these gels offers an additional advantage of exploration of designer biomaterials as injectable gels. The nanofibers of coassembled hydrogel were found to be highly biocompatible to the fibroblast cells compared to the individual peptides, which was evident from their cytotoxicity studies. We anticipate that our rational design of ECM protein mimics in the form of short bioactive peptides will contribute significantly to the development of novel biomaterials and play a crucial role in the field of tissue engineering and regenerative medicines